Intention to Visit Seoul: Factors Influencing Travel Abroad for Holidays - Herstanti, Ghassani; Rizan, Mohammad; Handaru, Agung Wahyu; Wibowo, Setyo Ferry (CV. Lenggogeni Data Publishing, 2023)
This paper aims to investigate the relationship between social media marketing activity and visit intention to Seoul, South Korea, among Indonesian travelers. A total of 246 questionnaires were distributed to respondents in Indonesia. Social media marketing activity represented the independent variable and was mediated by destination image, destination attitude, destination awareness, and perceived value. Visit intention represents the dependent variable. Partial Least Squares Structural Equation Modeling (PLS-SEM) is a statistical method used to analyze complex interrelationships between observed and latent variables. This finding indicates that the indirect impact of social media marketing activity on visit intention via the mediating factors of destination attitude and destination image is not statistically significant. The indirect effect of destination awareness and perceived value characteristics on social media marketing activity and visit intention is favorable and statistically significant. This is the first paper to investigate the relationship between social media marketing activity and visit intention in Seoul among Indonesian travelers. Moreover, this is a relatively new issue that remains largely undiscovered by researchers worldwide. This paper will help to emphasize its importance and implications for business decisions.